Alterações na legislação societária e a evidenciação das demonstrações contábeis em sociedades de economia mista: estudo de caso no Banco do Nordeste do Brasil (BNB) - Maia, Francisco Lúcio Mendes (2009)
The disclosure of information contained in the accounting statements is important for making decisions of users of accounting. This information, to become more accessible and consistent, seek to obey the universal rules; that means that the same level of information contained in a accounting statement, an entity in Brazil, tends to be evidenced in the accounting statements of entities in other countries considering the international accounting standards. In Brazil, the changes introduced by the federal nº 11.638/07 and 11.941/09, in relation to Law nº 6.404/76, are intended to clarify and clear the contents of this information. The semi-public companies are governed by the said legislation, in accordance with the your way of constitution, although they are also subject to legislation that govern the public administration for having significant participation in the public budget. The research was aimed at analyzing the changes in corporate law, and possible implications for the disclosure of accounting statements in semi-public companies. As specific objectives were defined the following: verify the accounting statements, mandatory, published by companies of mixed economy, before the term of the Federal Law nº 11.638/07 and of the Federal Law nº 11.941/09; identify the main changes determined by these laws, in relation to the financial statements mandatory for companies of mixed economy; verify the accounting statements, mandatory, published by semi-public companies, after entering into force of Law nº 11.638/07, and the Law nº 11.941/09; and identify the views of the manager and the servers of a company of mixed economy, adopted as an object of study, about the influence of such legislation on disclosure of accounting statements, before and after changes introduced by these laws. The methodology used was literature and documentary, as well as a case study in the Bank of Northeast Brazil, with application interview with the Director of Environment Accounting and questionnaires with the servers of the Superintendency of Financial and Capital Markets. By analyzing the financial statements of the entity object of study, notes that the Bank of Northeast Brazil, in fiscal 2008, did not show the classification of groups of balance sheet accounts established by the Provisional Measure nº 449/08, converted by Law nº 11.941/09. However, in the opinion of respondents, we can confirm that there was improvement in the disclosure of accounting statements, after the changes introduced by the legislation that amended the Federal Law nº 6.404/76.